(untitled) - Cole, Michael (New York, 1996)
Now in its third edition, The Development of Children is uniquely attentive to both scientific ramifications and potential practical applications of research findings, as well as the real-life social consequences of changing trends in scientific thought. The result is a skilfully woven and compelling story of how children grow, with a consistent emphasis on the influence of culture on development. Throughout, the text examines the influences of diverse child-rearing strategies, underscoring that there is no single 'correct' method. The book is masterfully written, with a flow among topics that allows the reader to apprehend the points with little effort. Psychological Science Website: http://www.whfreeman.com/thedevelopmentofchildren Supplements: Study Guide/Instructor's Resource Manual/Printed Test Bank/Computerized Test Banks/Overhead Transparencies
Keywords: Child development